2019
DOI: 10.1159/000496824
|View full text |Cite
|
Sign up to set email alerts
|

Language in Amnestic Mild Cognitive Impairment and Dementia of Alzheimer’s Type: Quantitatively or Qualitatively Different?

Abstract: Background/Aims: The purpose of this study was to explore language differences between individuals diagnosed with amnestic mild cognitive impairment multiple domain (aMCIm) and those with probable Alzheimer’s disease, with a goal of (i) characterizing the language profile of aMCIm and (ii) determining whether the profiles of dementia of Alzheimer’s type (DAT) and aMCIm individuals are on a continuum of one diagnostic entity or represent two distinct ­cognitive disorders. Methods: Language data from 28 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 60 publications
5
17
0
9
Order By: Relevance
“…Even though Naming and Semantic Association scores were significantly lower in the AD group compared to the MCI group, MCI patients performed significantly lower than cognitively unimpaired controls. This confirms increasing evidence that language deficits begin several years before the onset of AD dementia (Auriacombe et al, 2006) and that differences in language features between AD and MCI reflect predominantly quantitative instead of qualitative differences (Jokel et al, 2019). Earlier studies (Alexopoulos et al, 2006) have shown that individuals with multidomain MCI, including language deficits, are more likely to develop AD than those with an isolated memory deficit.…”
Section: Discussionsupporting
confidence: 75%
“…Even though Naming and Semantic Association scores were significantly lower in the AD group compared to the MCI group, MCI patients performed significantly lower than cognitively unimpaired controls. This confirms increasing evidence that language deficits begin several years before the onset of AD dementia (Auriacombe et al, 2006) and that differences in language features between AD and MCI reflect predominantly quantitative instead of qualitative differences (Jokel et al, 2019). Earlier studies (Alexopoulos et al, 2006) have shown that individuals with multidomain MCI, including language deficits, are more likely to develop AD than those with an isolated memory deficit.…”
Section: Discussionsupporting
confidence: 75%
“…Differences in measures of reading ability and vocabulary skills have been shown between individuals with MCI and HC previously. For example, individuals with MCI perform worse than HC on the Peabody Picture Vocabulary Test, a paper-pencil test which is similar to the PV task administered in the NIHTB-CB (Jokel, Seixas Lima, Fernandez, & Murphy, 2019). Although such vocabulary skills are thought to generally remain stable across the lifespan and represent estimated premorbid cognitive functioning (i.e., crystallized abilities), there is also evidence that performance on the Peabody Picture Vocabulary Test declines with increasing cognitive deficit, such as when comparing individuals with MCI to those with AD (Snitz, Bieliauskas, Crossland, Basso, & Roper, 2000) and could reflect changes in language functioning.…”
Section: Discussionmentioning
confidence: 99%
“…It may be hypothesised, then, that serious reductions in the capacity of WM cause the deficits summarised above, which include impaired interpretation of non‐canonical sentence structures and potential length effects. This is one of the most commonly cited explanations and one for which ample evidence exists (Jokel et al., 2019). Following this hypothesis, language impairments in AD can be seen as a more severe type of the declines often observed in typical ageing, though exacerbated by a reduced inhibitory control faculty and a highly impaired attention span (Ober and Shenaut, 1988).…”
Section: Alzheimer's Diseasementioning
confidence: 95%
“…Language ability and a severe deterioration thereof is one of the earliest and clearest markers of the onset of AD. Patients developing AD generally show an increasing inability to name familiar objects or people, reflecting the rapid deterioration of semantic memory associated with the condition (Jokel et al., 2019). Problems with pronunciation also develop due to increasing difficulties with swallowing and tongue movements, caused by an underlying motor impairment (Moorhouse & Fisher, 2017).…”
Section: Alzheimer's Diseasementioning
confidence: 99%